Dynamic Thermal Corridor May Connect Endangered Loggerhead Sea Turtles Across the Pacific Ocean - Briscoe, Dana K.; Turner Tomaszewicz, Calandra N.; Seminoff, Jeffrey A.; Parker, Denise M.; Balazs, George H.; Polovina, Jeffrey J.; Kurita, Masanori; Okamoto, Hitoshi; Saito, Tomomi; Rice, Marc R.; Crowder, Larry B. (Frontiers in Marine Science, 2021)
The North Pacific Loggerhead sea turtle (Caretta caretta) undergoes one of the greatest of all animal migrations, nesting exclusively in Japan and re-emerging several years later along important foraging grounds in the eastern North Pacific. Yet the mechanisms that connect these disparate habitats during what is known as the “lost years” have remained poorly understood. Here, we develop a new hypothesis regarding a possible physical mechanism for habitat connectivity – an intermittent “thermal corridor” – using remotely sensed oceanography and 6 juvenile loggerhead sea turtles that formed part of a 15 year tracking dataset of 231 individuals (1997–2013). While 97% of individuals remained in the Central North Pacific, these 6 turtles (about 3%), continued an eastward trajectory during periods associated with anomalously warm ocean conditions. These few individuals provided a unique opportunity to examine previously unknown recruitment pathways. To support this hypothesis, we employed an independently derived data set using novel stable isotope analyses of bone growth layers and assessed annual recruitment over the same time period (n = 33, 1997–2012). We suggest evidence of a thermal corridor that may allow for pulsed recruitment of loggerheads to the North American coast as a function of ocean conditions. Our findings offer, for the first time, the opportunity to explore the development of a dynamic ocean corridor for this protected species, illuminating a longstanding mystery in sea turtle ecology.